Enterprise Systems End-User Training : Development and evaluation of design principles towards a multimedia elearning approach for future potential users considering cognitive and attitudinal aspects - Wienand, Mareen (2024)
The adoption and implementation of enterprise systems (ES) such as SAP S/4HANA are pivotal for organizations seeking to enhance efficiency, streamline processes, and maintain competitiveness. However, traditional end-user training methods often fail to meet the cognitive and attitudinal needs of users, thereby limiting the potential of these systems. This dissertation develops and evaluates a novel multimedia eLearning approach aimed at improving enterprise system end-user training. Grounded in design science research, it establishes design principles that cater to the cognitive load and user experience, ensuring effective learning outcomes. Through a multi-phase methodology—including literature review, case studies, experiments, and evaluations—the research assesses the effectiveness of the proposed training against traditional methods. The findings demonstrate the superiority of eLearning-based training in enhancing usability perception, user experience, and cognitive engagement, providing actionable insights for both academia and practice. This work contributes to the body of knowledge by bridging the gap between educational design and enterprise system training, offering a scalable solution for future users in increasingly digitalized organizational environments.
Keywords: Enterprise-Resource-Planning; E-Learning; Selbststud; Anwenderschulung; SAP Fiori